(untitled) (Bangladesh Agronomy Journal, 2020)
The experiment was conducted at Jute Agriculture Experimental Station (JAES), Manikganj; Jute Research Regional Station (JRRS), Rangpur and Jute Research Sub Station (JRSS), Jessore in 2017 to determine optimum field duration on yield and yield attributes of different tossa jute varieties. The experiment was laid-out in RCBD with three replications. Tossa jute varieties O-9897, BJRI Tossa Pat-5 and JRO-524 were used as planting materials. Crops were sown on last week of March to First week of April. The crops were harvested at different field durations (90 days, 100 days and 110 days after sowing) regarded as treatment. All crops were attained recommended cultural practices. Result showed that BJRI Tossa Pat-5 gave higher fibre production in 90 days at Manikganj and Rangpur (2.69 tha-1and 2.34tha-1 respectively)and 100 days field duration which was followed by JRO -524 (2.36 tha-1 and 2.24 tha-1 respectively)and O- 9897(2.21 tha-1and 4.54 tha-1, respectively), however at 110 days JRO-524 (3.40 tha-1; 3.34 tha-1and 3.16 tha-1 respectively) gave the higher fibre yield compare other two varieties BJRI Tossa Pat-5 (3.20 tha-1; 3.14 tha-1and 3.12 tha-1 respectively) and O- 9897 (3.05 tha-1; 2.99 tha-1and 2.99 tha-1 respectively) at Manikganj , Rangpur and Jessore. Bangladesh Agron. J. 2019, 22(2): 77-82